Multum facetias in dicendo prodesse saepe, Cic. De or. II 227 – dowcip w retorycznej teorii i praktyce - Nowak, Magdalena (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2010)
The article analyses and compares different passages of Cicero’s dialogue De oratore and Quintilian’s Institutio oratoria, which bring up the issue of using humour and jokes by speakers in order to gain a rhetoric victory and win the listeners over.

Marcus Tullius Cicero, as a speaker, was famous for his skill of using humour and jokes in his oratorical speeches. In Quintilian’s opinion, in this aspect, he was even better than the most famous Greek orator – Demostenes. Therefore, he was qualified to insert a lecture about humour and joking in one of his papers concerning the theory of rhetoric. Such a lecture is included in De oratore dialogue written in 55 BC (De or. II 216–290). A similar passage about humour in rhetoric is found in Quintilian’s Institutio oratoria which was written one hundred years later (Institutio oratoria VI 3, 1–112). This article mentions Cicero’s Greek predecessors and their writings in which they recommended the use of humour by the speaker and this is from where Cicero could get his theoretical knowledge on this matter. It also shows how the issue of humour and jokes in a speech was presented in Roman books of rhetoric such as Rhetorica ad Herennium and in other than De oratore dialogue texts by Cicero. Then, the article analyses and compares Cicero’s and Quintilian’s views on humour issues such as what makes the person capable of using humour, whether you can learn it and how it should be done. The author compares Cicero’s and Quintilian’s views on what humorousness is, what its source and types are, whether the speaker should use it to entertain their listeners and where the humour and joking limits lie.
Multum facetias in dicendo prodesse saepe, Cic. De or. II 227 – humor in rhetoric theory and practice
Keywords: Roman rhetoric; Cicero; Humor; Quintilianus; Wit